2020
DOI: 10.1093/ofid/ofaa173
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Nontuberculous Mycobacterial Infections at a Midwestern Tertiary Hospital: A Retrospective Study of 365 Patients

Abstract: Background The prevalence of infections due to nontuberculous mycobacteria (NTM) is increasing worldwide, yet little is known about the epidemiology and pathophysiology of these ubiquitous environmental organisms. Pulmonary disease due to Mycobacterium avium complex is most prevalent, but many other NTM species can cause disease in virtually any organ system. As NTM becomes an increasingly common cause of morbidity and mortality, more information is needed about the epidemiology of NTM diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…In Africa, most of the NTMs are reported as incidental findings in livestock with gross pathological lesions identified in slaughterhouses, when tissues are submitted for M. bovis surveillance [18,19]. There are substantially fewer reports of NTMs isolated from free-ranging wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, most of the NTMs are reported as incidental findings in livestock with gross pathological lesions identified in slaughterhouses, when tissues are submitted for M. bovis surveillance [18,19]. There are substantially fewer reports of NTMs isolated from free-ranging wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with our study that identified species belonging to MAC (31%) (M. avium subspecies (32%), M. intracellulare (27%), M. yongonese (18%), M. parascrofulaceum (5%), M. paratuberculosis (2%), and M.timonense (2%)) as the most widely isolated NTM in Kenya. Other countries with similar findings include China [39]- [41], Russia [42], America [43], [44], various countries in Europe [45] and Africa [11], [20], [46]- [48]. The high infectivity rate of MAC species could be attributed to their seemingly abundant nature and distribution in different environmental sources such as water and soil, consequently increasing its ease of spread and infection to humans [20], [49].…”
Section: Discussionmentioning
confidence: 79%
“…BAE was more frequently used in patients with NTM or aspergillus infections although there was a very small proportion with either of these infections in the cohort to enable detailed analyses. Hemoptysis is commonly experienced in those with NTM lung disease, and there are successful reports of BAE in the literature [30,31]. Aspergillus-associated hemoptysis is typically related to aspergillomas, as well as chronic pulmonary aspergillosis [32].…”
Section: Resultsmentioning
confidence: 99%